SLC1A4: A Powerful Prognostic Marker and Promising Therapeutic Target for HCC - Peng, Xiaozhen; Chen, Ruochan; Cai, Shenglan; Lu, Shanshan; Zhang, Yiya (Frontiers in Oncology, 2021)
SLC1A4, a Na-dependent neutral amino acid transporter, was considered to participate in the various pathobiological process, including tumorigenesis. However, the correlation between SLC1A4 and Hepatocellular Carcinoma (HCC) remains unclear. In our study, integrative bioinformatics and functional profiling were performed to reveal the prognosis and potential function of SLC1A4 in HCC. The results showed that the mRNA and protein levels of SLC1A4 were elevated in HCC, and it was a powerful independent prognostic marker for overall survival (OS). The co-expressed genes analysis and GSEA analysis showed that SLC1A4 was related to cell cycle, metabolism, cancer-related pathway. Furthermore, the functional analysis revealed that silenced SLC1A4 inhibited cell proliferation, migration, cell cycle, and promoted cell apoptosis in HCC. Next, immune analysis showed that SLC1A4 expression was positively associated with immune infiltration and immune-related chemokine expression in HCC. Silenced SLC1A4 evidently reduced these chemokines expression in HCC cells. Finally, drug sensitivity analysis revealed potential five sensitivity drugs for HCC patients with high-expressed SLC1A4. In conclusion, our results suggested that SLCIA4 could be a novel predictor prognosis and immunotherapeutic targets of HCC, and the sensitivity drugs may be effective therapeutic strategy for HCC patients with high-expressed SLC1A4.